(3eLeY GdHdGZIs
(3ChdgG (B:s
(3abO GfJNHJgG heG GfJejJ Gdjg ef GYdGe MHQ GbJVjJgG hLeYJgG heG hLOJg ef cdGe GdHdZGA JQLeI GdMOhO hGdCHhGH GdChd MO GdYbd hVOg heG jJYdb HgeG s
(3BNQgG (B:s
(3hai cdGe ddMSf Gf bheG QcHhG GdGaQGS hdHShG dKjGH GdQbGb WYGe GMOge ZUH jJcj Ydi TeGdg hjCcd ZjQ eGdg MJi GPG GNPJg GdcXI jbhd GHZjGdi gGVh eG hjdc hgd JgVe GdGOfjc fLR cJGH eLeY GdHdGZI s
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd s
Keywords: (3GdCOHs